Controlling the fate of roxarsone and inorganic arsenic in poultry litter - Salazar, Jason Mark; Quazi, Shahida; Andra, Syam S.; Sarkar, Dibyendu; Bach, Stephan B H; Datta, Rupali K.; Makris, Konstantinos C. (My University, 2008)
A growing body of literature reports 3-nitro-4-hydroxyphenylarsonic acid (roxarsone) degradation in poultry litter (PL) to the more toxic inorganic arsenic (As). Aluminum-based drinking-water treatment residuals (WTR) present a low-cost amendment technology to reduce As availability in PL, similar to the use of alum to reduce phosphorus availability. Batch experiments investigated the effectiveness of WTR in removing roxarsone and inorganic As species from PL aqueous suspensions. Incubation experiments with WTR-amended PL evaluated the effects of WTR application rates (2.5–15% by weight) and incubation time (up to 32 d) at two incubation temperatures (23 and 35°C) on As availability in PL. Batch PL aqueous experiments showed the high affinity of As(V), As(III), dimethylarsinic acid (DMA), monomethylarsonic acid (MMA), and roxarsone for the WTR. The 10% WTR amendment rate decreased As availability in PL by half of that of the unamended (no WTR) PL-incubated samples. The reduction in dissolved As concentrations during incubation of WTR-amended PL samples was kinetically limited, being complete within 13 d. Parallel reductions in roxarsone, As(V), and DMA concentrations were observed with liquid chromatography–inductively coupled plasma mass spectrometry, whereas As(III) and MMA concentrations were always <5% of dissolved As. Incubation temperature did not significantly (p > 0.05) influence dissolved As concentrations in the WTR-amended PL. Potential formation of a copper-containing roxarsone metabolite was considered in PL aqueous suspensions with the aid of electrospray mass spectrometry. Further experiments in the field are necessary to ensure that sorbed As is stable in WTR-amended PL.
Keywords: Mass spectrometry; Potable water; Toxicity; Water treatment; Aqueous suspensions; Poultry litter; Water treatment residuals (WTR); Arsenic compounds